Endemicity response timelines for Plasmodium falciparum elimination - Smith, D; Hay, S; Hay, S (BioMed Central, 2009)
Background. The scaling up of malaria control and renewed calls for malaria eradication have raised interest in defining timelines for changes in malaria endemicity. Methods. The epidemiological theory for the decline in the Plasmodium falciparum parasite rate (PfPR, the prevalence of infection) following intervention was critically reviewed and where necessary extended to consider superinfection, heterogeneous biting, and aging infections. Timelines for malaria control and elimination under different levels of intervention were then established using a wide range of candidate mathematical models. Analysis focused on the timelines from baseline to 1% and from 1% through the final stages of elimination. Results. The Ross-Macdonald model, which ignores superinfection, was used for planning during the Global Malaria Eradication Programme (GMEP). In models that consider superinfection, PfPR takes two to three years longer to reach 1% starting from a hyperendemic baseline, consistent with one of the few large-scale malaria control trials conducted in an African population with hyperendemic malaria. The time to elimination depends fundamentally upon the extent to which malaria transmission is interrupted and the size of the human population modelled. When the PfPR drops below 1%, almost all models predict similar and proportional declines in PfPR in consecutive years from 1% through to elimination and that the waiting time to reduce PfPR from 10% to 1% and from 1% to 0.1% are approximately equal, but the decay rate can increase over time if infections senesce. Conclusion. The theory described herein provides simple "rules of thumb" and likely time horizons for the impact of interventions for control and elimination. Starting from a hyperendemic baseline, the GMEP planning timelines, which were based on the Ross-Macdonald model with completely interrupted transmission, were inappropriate for setting endemicity timelines and they represent the most optimistic scenario for places with lower endemicity. Basic timelines from PfPR of 1% through elimination depend on population size and low-level transmission. These models provide a theoretical basis that can be further tailored to specific control and elimination scenarios.